The Manifestations of Book Culture in The Diary of Vytautas Civinskis - Girininkaitė, Veronika (Bibliotheca Lituana, 2018)
[full article and abstract in Lithuanian; summary in English]The article aims to explore the possibilities of analyzing an egodocument as a source for the studies of book culture. The article consists of an analysis of an egodocument from the beginning of 20th century, a manuscript of The Diary, written by a voracious reader and young intellectual, veterinarian student Vytautas Civinskis (or Witold Cywiński, 1887–1910). This Diary is a large document, containing more than 3 500 pages, where the original autobiographic text is combined with the received correspondence, printed matter, postcards collected and the photographs made by the diarist.Book culture is a relatively new concept that unites various data and practices related to the different uses of a book, its material and spiritual value for the individual. This article demonstrates that, while analyzing the selected Diary, perhaps every possible aspect of book culture can be mentioned. Some informatikon was collected on the buying of books, on reading promotion, on selling some printed materials and so on.The numerous reader’s notes, written by Civinskis, show which books were read by the diarist and what conclusions could be drawn. The epistolary part of this egodocument demonstrates how important for this family was the reading of the latest news printed in various newspapers. The practice of reusing newspapers (sending most interesting of the read newspapers to the relatives) was discovered. It is noted, for example, that Vytautas Civinskis received the most important articles from his father, and that he himself would send or subscribe to some of the magazines for his younger brother. Sharing of the information and favorite books was an important part of family life. This practice was also obvious, when some of the books, prohibited in the Russian Empire, were smuggled from abroad (also by the diarist himself) to be shared with relatives or sold. The Diary, beginning of which was written in the times of the ban of the Lithuanian language, sheds some light on phenomena important for that epoch in Lithuania. The interest of the diarist for Lithuanian literature and his sympathy to the Lithuanian language revival is clearly seen through his reading preferences. The Diary allows the researchers to investigate which books were bought and which periodicals were subscribed to by the diarist. Attention was drawn on the extremely rich repertoire of the literature read by Civinskis. Among the read books were the classics of Polish, Russian, Lithuanian and world literatures as well as the scientific and socialist ideology books.The fact that Vytautas Civinskis participated in the working matters of two small libraries, one of the Lithuanian Tartu Student Society and one of the Society of Skapiškis Farmers, is also mentioned. It seems that the regulations of the latter now can be found only in draft in the Diary of Vytautas Civinskis. Both of the libraries depended strongly on donations and charity, collected during specially arranged public performances. In summary, it can be noted that the selected egodocument, as well as the other documents of this kind, seem to be a promising source for further, more extensive studies of book culture and any related cultural practices.